Effect of skin testing and segregation on the incidence of bovine tuberculosis, and molecular typing of Mycobacterium bovis in Ethiopia - AMENI, GOBENA (2007)
Bovine tuberculosis (TB) remains a disease of economic and public health importance in developing countries. The aim of this study was to evaluate the use of tuberculin skin-testing and segregation of reactors as a potential control method, and initiate molecular typing of Mycobacterium bovis (M. bovis) in Ethiopia. Comparative intradermal tuberculin test (CIDT), pathological examination, bacteriology, molecular typing were applied. The prevalence of bovine TB was 48% (n=500) in the Holeta Farm as disclosed at the first CIDT conducted in 2002, whereupon the Farm was divided into positive and negative herds. Following three consecutive rounds of skin testing and segregation of skin test positive and negative animals, the incidence of bovine TB was dramatically reduced from 14% to 1% in the negative herd in a year. Spoligotyping of 41 isolates from 17 cows had an identical and uniques poligotypepattern, which can be represented as a binary of 1100000101111110111111100010000000000100000 where 1 indicates the presence of a spacer and 0 represents loss. This spoligotype pattern was not reported previously from elsewhere to the M. bovis database (www.mbovis.org). The new spoligotype pattern was therefore designated as EMbs1, Ethiopian M. bovis strain 1. The VNTR profile of the strain was 5254*33.1 and differed from the VNTR profile of strains reported from United Kingdom. The result of this has shown the potential application of test and segregation for the control of bovine TB particularly in developing countries.